2003
DOI: 10.3406/tiers.2003.5391
|View full text |Cite
|
Sign up to set email alerts
|

Homicides en Amérique du Sud : les pauvres sont-ils dangereux ?

Abstract: Mamadou Camara, Pierre Salama — Homicides in South America. Are the poor dangerous ? Are the poor the principal causes of violence ? Can repressive policies be effective and significantly reduce homicide rates or should the dominant modes of development in these countries be re-examined ? The aim of this article is, first, to overview the state of the matter, then to analyse and discuss the influence of different economic variables on homicide rates, from an econometric test concerning a number of South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…That is, the consistency of the results of the effect of inequalities in access to water and access to electricity has not yet been established in the literature because no study has yet looked at it. Nevertheless, the results of the effects of the Gini index, population density and poverty rate are consistent with the ndings of(Camara and Salama, 2003, Coccia, 2018, Daniya et al, 2020 Camara and Salama (2003),. showed that income inequality increases homicide.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…That is, the consistency of the results of the effect of inequalities in access to water and access to electricity has not yet been established in the literature because no study has yet looked at it. Nevertheless, the results of the effects of the Gini index, population density and poverty rate are consistent with the ndings of(Camara and Salama, 2003, Coccia, 2018, Daniya et al, 2020 Camara and Salama (2003),. showed that income inequality increases homicide.…”
supporting
confidence: 86%
“…Therefore, if an individual experiences an increase in income, for example, he or she will be able to afford a better life. An increase in economic growth (log GDPH) of 1% results in a decrease in homicides of 2.57%, in contrast to the effect due to an increase in the speed of growth (CROISS) that we saw earlier (Camara and Salama, 2003). This effect argues that part of the violence in the region emanates from poor living conditions (Camara and Salama, 2003).…”
Section: Basic Resultsmentioning
confidence: 76%
See 3 more Smart Citations